The Influence of Leadership Style, Communication and Occupational Safety and Health on Employee Job Satisfaction at Pt. Vibro Nusantara Indonesia - Nyoto Nyoto; Agung Suranto; Nicholas Renaldo; Achmad Tavip Junaedi; Suhardjo Suhardjo; Rebecca La Volla Nyoto (Journal of Entrepreneurial and Business Diversity, 2026)
Purpose:This research aims to determine the influence of leadership style, communication, occupational safety and health on job satisfaction at PT. Vibro Nusantara Indonesia.Methodology:This research uses primary and secondary data originating from employees of PT. Vibro Nusantara Indonesia is included in the sample. The sampling technique in this research used the convenience sampling method. The number of samples obtained was 100 employees. This research analysis method uses descriptive analysis and several types of evaluation using SPSS software.Findings:From this research, it was concluded that variables namely leadership style, communication have a positif influence on employee job satisfaction and occupational safety and health have a negatif influence on employee job satisfaction.Implication:The findings indicate that leadership style and communication should be strengthened to improve employee job satisfaction, while occupational safety and health practices require further managerial attention.